1979
DOI: 10.1097/00132586-197906000-00040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surgical Stress on Haemodynamics during Neurolept Anaesthesia

Abstract: The influence of surgical stress on haemodynamics during neurolept anaesthesia (NLA) was studied in ten patients, while they were awake, under anaesthesia prior to surgery and peroperatively. Systemic arterial, pulmonary arterial, right atrial and pulmonary capillary wedge pressures, as well as cardiac output (&), arterial oxygen content and mixed venous oxygen content, were measured. Systemic and pulmonary vascular resistances, arterial-venous oxygen content difference (AVD) , oxygen consumption (voJ and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
1

Year Published

1979
1979
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
3
4
1
Order By: Relevance
“…The fall in T P R following NLA agrees with results in other studies (DIXON et al 1970, SANTESSON et al 1978). There may be several explanations for this decrease.…”
Section: A)supporting
confidence: 91%
See 3 more Smart Citations
“…The fall in T P R following NLA agrees with results in other studies (DIXON et al 1970, SANTESSON et al 1978). There may be several explanations for this decrease.…”
Section: A)supporting
confidence: 91%
“…If the decrease in 0, was caused by a primary myocardial depression, a n increase in AVD would have been expected to compensate for the decrease in total oxygen availability. The unchanged AVD following NLA is in accordance with recent results in surgical patients (BRISMAR et al 1977, SANTESSON et al 1978. The fact that SV and CVP were both unchanged lends further support to the assumption that NLA did not cause any primary depression of cardiac function, which is also in agreement with several studies in the dog , DIXON et al 1970, FREYE 1974, OSTHEIMER et al 1975).…”
Section: A)supporting
confidence: 89%
See 2 more Smart Citations
“…The total body oxygen uptake is reduced by 20-40% by general anesthesia. 26,27 Several studies have been made on the effects of different anesthetics on hormones, as well as on blood glucose. Thus, it has been found that thiopental in combination with nitrous oxide/oxygen does not influence blood sugar.4, 28, 29 Anesthesia with droperidol, fentanyl, and nitrous oxide in oxygen for 1 hr does not alter the adrenaline and noradrenaline levels.…”
Section: Resultsmentioning
confidence: 99%